Surveillance and Protection-Based Approach for Link Failures over Fiber-to the-Home (FTTH) with Combination of ACS and SANTAD - Aswir Premadi; Boonchuan Ng; Mohammad Syuhaini Ab-Rahman (LPPM ITB, 2009)
This paper introduces an in-service transmission surveillance and protection-based approach for fiber failures/faults over fiber-to-the-home passive optical network (FTTH-PON) with an excellent combination of Access Control System (ACS) and Smart Access Network Testing, Analyzing and Database (SANTAD). Our hardware design works on a standard local area network (LAN) using a specially designed hardware interfaced with a microcontroller integrated Ethernet to monitor the status of optical signals flow and provide the restoration against fiber failures/faults in FTTH-PON. We also introduce the centralized management and access control program by means of SANTAD. ACS is used to control the troubleshooting mechanism carried out by SANTAD. This design will be implemented at central office (CO) for distant monitoring and remote controlling each optical fiber line's status as well as for detecting any failures/faults that occurs in the network system downwardly from CO towards multiple optical network units (ONUs). The scope of this discussion only highlighted on the monitoring and controlling instead of the restoration scheme.